Pengaruh Sosial Media Marketing terhadap Keputusan Pembelian Konsumen di Industri Perhotelan di Kota Bandung - Nisa Fakhira Atqiya (Asosiasi Ahli Administrasi Indonesia, 2022)
The rapid development of social media helps the public to obtain relevant information related to the hotel industry and is expected to be able to make good use of social media in business activities. On this basis, the aim of this research is to determine the influence of social media on consumer purchasing decisions in the hotel industry in Bandung City. This research uses a quantitative descriptive method and uses a questionnaire for data collection. In this research, 105 respondents were involved who live outside/inside the city of Bandung, for data analysis using the mean test and regression analysis test. The research results explain that social media has a significant and positive influence on purchasing decisions in the hotel industry in the city of Bandung.